Phytochemical Profile and Antioxidant Activity of Lavandula angustifolia and Lavandula x intermedia Cultivars Extracted with Different Methods - Natalia Dobros; Katarzyna Zawada; Katarzyna Paradowska (MDPI AG, 2022)
Lavender is a valuable perennial plant from the Lamiaceae family. It is grown mainly for its essential oil, but it also contains polar bioactive compounds such as polyphenols and coumarins. Their level depends on the species, cultivars, geographical origin, climatic conditions, harvest time and extraction method. The authors investigated the effect of several extraction procedures (maceration, decoction and ultrasound-assisted extraction) applied to three cultivars of Lavandula angustifolia (Betty's Blue, Elizabeth, Hidcote) and two cultivars of Lavandula x intermedia (Grosso, Gros Bleu) on the yield of the polyphenolic compounds and antioxidant activity. HPLC analysis showed the presence of rosmarinic acid (2.52-10.82 mg/g), ferulic acid glucoside (2.94-8.67 mg/g), caffeic acid (1.70-3.10 mg/g), morin (1.02-13.63 mg/g), coumarin (1.01-5.97 mg/g) and herniarin (1.05-8.02 mg/g). The content of phenolic acids and flavonoids was higher in lavender, while the content of coumarins was higher in lavandin in all types of extracts. The antioxidant activity was determined by DPPH-EPR assay for antiradical properties (104.58-206.77 μmol Trolox/g) and FRAP assay for reducing properties (79.21-203.06 μmol Trolox/g). The obtained results showed that the cultivar is the dominant factor differentiating the samples. Still, the extraction method plays an important role in the final bioactive substances content and antioxidant properties of obtained extracts.